2000
DOI: 10.1021/jp001288h
|View full text |Cite
|
Sign up to set email alerts
|

On−Off Blinking and Multiple Bright States of Single Europium Ions in Eu3+:Y2O3 Nanocrystals

Abstract: We show that continuously illuminated single europium ions incorporated in yttrium oxide (Eu 3+ :Y 2 O 3 ) nanocrystals (5-15 nm diameter) undergo on-off blinking on a variable time scale ranging from hundreds of milliseconds to several seconds. We observe both a pump-intensity dependent "duty factor" (on-time as a percentage of total measurement time), and quantum jumps between at least three well-defined luminescence intensity levels (bright states) from individual nanoparticles. Interesting switching or osc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 14 publications
2
29
1
Order By: Relevance
“…Owing to these properties there has been a growing interest in luminescent transition metal and/or rare earth ions-doped nanoparticles because of their practical applications as high brightness luminophors and displays [3][4][5][6][7]. In particular, Bhargava et al [8] have shown strong orange luminescence in Mn 2+ -doped ZnS nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to these properties there has been a growing interest in luminescent transition metal and/or rare earth ions-doped nanoparticles because of their practical applications as high brightness luminophors and displays [3][4][5][6][7]. In particular, Bhargava et al [8] have shown strong orange luminescence in Mn 2+ -doped ZnS nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The size dependant efficiency of individually separated nanocrystals has been recently measured by combining atomic forced microscopy (AFM) and high N.A. fluorescence optical microscopy at Oak Ridge National Laboratory [31,32]. In view of this, stability of particle size is very important in wide range of temperature for better device performance.…”
Section: Resultsmentioning
confidence: 99%
“…These methods generally require complex and costly installations without necessarily ensure the achievement of homogeneous particles. On the other hand chemical methods [7][8][9][10], are less expensive, more affordable and consist of particles grow using molecules as departure entities. The soft chemistry provides particularly materials while controlling the morphology, grain size and stoichiometry.…”
Section: Introductionmentioning
confidence: 99%